Hart Corporation / Muhammad Alif Afiq Mustapa... [et al.] - Mustapa, Muhammad Alif Afiq; Jaiton, Johantan; Sahijin, Mohd Hafiz; Alip, Muhd Syazwan; Mohd Ismail, Khairunnisa; Raja Azizul, Raja Maizatul Syamira (2015)
Our company's name is HART Corporation. The business is in the form of partnership company consisting of six member. Each member contributes certain amounts of cashagree in our agreement. Our main business is selling multi shower product. The purpose of our business is we want invent something new that not be done by other entrepreneur. Eventhough this product not well known and a new product, but we confident that our business will be success in the future. Our business is aimed to make sure our customer will satisfied with our multi shower product. We had dicussed that our business will be launced on 5 August 2015. The shops will be open 7 day a week (from monday to Sunday) and we are open from 8.00 am until 5.00 pm on monday to Saturday and will be open at 9.00 am to 3.00 pm on Sunday. All partner are entitled in the business management. We have agreed Muhammad Alif Afiq bin Mustapa as General Manager, Muhamad Syazwan bin Alip as Assistant Manager, Muhd. Hafiz bin Sahijin as Financial Manager, Khairunissa binti Ismail as Marketing Manager, Raja Maizatul Syamira Binti Raja Azizul as Administrative Manager and Johantan Jaiton as Operational Manager.